Anaesthetic management of pregnant patients with cardiac implantable electronic devices: case reports and review. (February 2018) - Salman, M.M.; Kemp, H.I.; Cauldwell, M.R.; Dob, D.P.; Sutton, R.
Highlights: Cardiac implantable electronic devices are becoming more common in pregnant women. Special considerations are required for their safe use in the perioperative period. Successful management of this patient group requires a multidisciplinary approach. Abstract: Heart disease is a leading cause of maternal mortality and morbidity. Pregnant women with structural, conduction or degenerative cardiac disease who require rhythm control or who are at high risk of sudden cardiac death may carry a cardiac implantable electronic device or may occasionally require the insertion of one during their pregnancy. These women are now encountered more frequently in clinical practice, and it is essential that a multidisciplinary approach, beginning from the early antenatal phase, be adopted in their counselling and management. Contemporary cardiac rhythm control devices are a constantly evolving technology with increasingly sophisticated features; anaesthetists should therefore have an adequate understanding of the principles of their operation and the special considerations for their use, in order to enable their safe management in the peripartum period. Of particular importance is the potential adverse effect of electromagnetic interference, which may cause device malfunction or damage, and the precautions required to reduce this risk. The ultimate goal in the management of this patient subgroup is to minimise the disruption to cardiovascular physiology that may occur near the time of labour and delivery and to control the factors that impact on device integrity and function. We present the ante- and peripartum management of two pregnant women with an implantable cardioverter-defibrillator, followed by a review and update of the anaesthetic management of parturients with cardiac implantable electronic devices.